2016
DOI: 10.1128/jvi.01616-16
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Escape from a Peptidic Anchor Inhibitor through Stabilization of the Envelope Glycoprotein Spike

Abstract: The trimeric HIV-1 envelope glycoprotein spike (Env) mediates viral entry into cells by using a spring-loaded mechanism that allows for the controlled insertion of the Env fusion peptide into the target membrane, followed by membrane fusion. Env is the focus of vaccine research aimed at inducing protective immunity by antibodies as well as efforts to develop drugs that inhibit the viral entry process. The molecular factors contributing to Env stability and decay need to be understood better in order to optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
39
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 72 publications
5
39
0
Order By: Relevance
“…We observed that the alterations selected in the presence of VIR-353 also affect HIV-1 susceptibility to the antibody VRC34 that targets an epitope that includes the N-terminal part of the FP (20). Notably, Eggink et al also suggested that the abovementioned alterations in the gp120 C1 and gp41 HR1 regions alter VIR165 sensitivity because they change the kinetics of Env conformational changes and thus decrease the accessibility of the FP target region (27).…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…We observed that the alterations selected in the presence of VIR-353 also affect HIV-1 susceptibility to the antibody VRC34 that targets an epitope that includes the N-terminal part of the FP (20). Notably, Eggink et al also suggested that the abovementioned alterations in the gp120 C1 and gp41 HR1 regions alter VIR165 sensitivity because they change the kinetics of Env conformational changes and thus decrease the accessibility of the FP target region (27).…”
Section: Discussionmentioning
confidence: 72%
“…In addition, it is well known that alterations in the helical regions of gp41 affects fusion kinetics and susceptibility to HIV-1 entry inhibitors (33,34). The finding that alterations reducing HIV-1 susceptibility to VIR-165 and VIR-353 increase viral sensitivity to inhibition by T20 targeting the HR1 region of gp41 (13,27) also supports effects on fusion kinetics. Thus, the results of the previous studies are not in disagreement with the gp41 FP being the primary target of VIR-based inhibitors.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations